Nalbufina e morfina intracameral em cães - Ferreira, Joana Zafalon [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Intracameral injection is used for treatment and anesthesia of the eye bulb and opioids are known to provide analgesia through this route. The aim of the study was to evaluate the viability and efficacy of intracameral nalbuphine and morphine in dogs. Seven beagle dogs were randomly included in the groups of intracameral nalbuphine (GNIC), intracameral morphine (GMIC), intravenous nalbuphine (GNIV) and intravenous morphine (GMIV) injection of either opioid. Variables were heart rate, respiratory rate, systolic arterial pressure, subjective pain scale, Schirmer's test, pupillary diameter, intraocular pressure, fluorescein test, corneal touch threshold, number and type of local or systemic complications and duration of effect on the cornea. Time point comprised baseline (T0) and measurements every 30 minutes after drugs administration up to 240 minutes. Parametric variables were analyzed through ANOVA for repeated measures and Dunnett's test. Ordinal data were compared through Friedman's test, followed by Dunn's test. Analyses were performed by SAS and were considered significant when P<0.05. Analgesia lasted significantly longer in GNIC, whereas GMIC, GNIV and GMIV did not differ between one another. There was a significant decrease in the IOP at T30 in all groups when compared to baseline measures. As for complications, no difference was found between groups. Therefore, both nalbuphine and morphine can be used for intracameral analgesia, and nalbuphine is the preferred option due to the prolonged analgesia.
Keywords: Analgesia; Anestesia veterinaria; Opióides; Cães; Morfina; Oftalmologia veterinaria; Anterior chamber